PENGARUH KEBIJAKAN HUTANG, KEPEMILIKAN MANAJERIAL, KEBIJAKAN DIVIDEN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi pada Sektor Pertambangan yang Terdaftar di BEI Periode 2011-2014) - MAJID PRACIHARA, SONYA (Jurnal Ilmu Manajemen (JIM), 2016)
The purpose of this research is analyze the effect of debt policy, managerial ownership, dividend policy, and firm size of the firm value. This research is a quantitative approach and secondary data. The sampling technique that used in this research is purposive sampling and the number of samples that used were as many as 12 companies. The object of this research Mining Sector that were registered on Indonesia Stock Exchange period 2011-2014. The analyze technique that used is linear regression. The variable that used in this research is the firm value (PBV) as dependent variable. Debt policy (DER), managerial ownership, dividend policy (DPR) and firm size as independent variable. The results of this research indicate that debt policy variable negative and significant related to firm value. Managerial ownership variable does not effect the firm value. Dividend policy variable positive and significant effect on firm value. Firm size variable does not effect the firm value. Keywords: Firm Value, Debt Policy, Managerial Ownership, Dividend Policy.